RyR2 regulates Cx43 hemichannel intracellular Ca2+-dependent activation in cardiomyocytes. Issue 1 (16th December 2019) - Lissoni, Alessio; Hulpiau, Paco; Martins-Marques, Tânia; Wang, Nan; Bultynck, Geert; Schulz, Rainer; Witschas, Katja; Girao, Henrique; De Smet, Maarten; Leybaert, Luc
Abstract: Aims: Connexin-based gap junctions are crucial for electrical communication in the heart; they are each composed of two docked hemichannels (HCs), supplied as unpaired channels via the sarcolemma. When open, an unpaired HC forms a large pore, high-conductance and Ca 2+ -permeable membrane shunt pathway that may disturb cardiomyocyte function. HCs composed of connexin 43 (Cx43), a major cardiac connexin, can be opened by electrical stimulation but only by very positive membrane potentials. Here, we investigated the activation of Cx43 HCs in murine ventricular cardiomyocytes voltage-clamped at −70 mV. Methods and results: Using whole-cell patch-clamp, co-immunoprecipitation, western blot analysis, immunocytochemistry, proximity ligation assays, and protein docking studies, we found that stimulation of ryanodine receptors (RyRs) triggered unitary currents with a single-channel conductance of ∼220 pS, which were strongly reduced by Cx43 knockdown. Recordings under Ca 2+ -clamp conditions showed that both RyR activation and intracellular Ca 2+ elevation were necessary for HC opening. Proximity ligation studies indicated close Cx43-RyR2 apposition (<40 nm), and both proteins co-immunoprecipitated indicating physical interaction. Molecular modelling suggested a strongly conserved RyR-mimicking peptide sequence (RyRHCIp), which inhibited RyR/Ca 2+ HC activation but not voltage-triggered activation. The peptide also slowed down action potential repolarization. Interestingly, alterations in the concerned RyR sequence are known to be associated with primary familial hypertrophic cardiomyopathy. Conclusion: Our results demonstrate that Cx43 HCs are intimately linked to RyRs, allowing them to open at negative diastolic membrane potential in response to RyR activation. Graphical Abstract: